Study to Know the Effect of “Compression Only Life Support” Training among the Lay Persons - Jarwani, Bhavesh S; Gajjar, Mehul; Gupta, Sapna D; Makwana, Harsha; Thakor, Advait; Modi, Urjita P (National Journal of Community Medicine, 2019)
Introduction: Out of hospital cardiac arrest (OHCA) is one of the leading causes of death in India. And “Compression-only CPR (COLS)” is as effective as conventional CPR for cardiac arrest at home, at work or in public. This study intends to know the attitude and knowledge among the laypersons towards performing com- pression only CPR, use of AEDs and effect of training sessions of COLS on attitude and imparting technical skills among them. Method: Pre-validated questionnaire-based study was conducted on “World Head Restart Day” (23rd Oct.,2018). 2 hours of training session was arranged and effect was statistically studies. Results: Total 298 volunteers successfully did participate in training and filled up the forms, of which 68% were male, 32 % female. Mean age 34+12 years. There was significant positive change in the atti- tude score from 4 to 22 (p=0.003). On the knowledge front average gain in score of volunteers pre-training v/s post-training was 1 v/s 9 (p<0.05). Main gains were in the knowledge of compression rate (2 % to 80%, p=0.001), compression depth (1% to 78%, p=0.002), how to operate AED (0% to 90%, p<0.001). Conclusion: These kinds of training programs (COLS) have a sig- nificant effect on lay rescuer to impart the COLS to the victims.